دراسة تجريبية لأثر الحرارة والأغلفة في إنبات بذور وأجنة الزيتون صنف "الخضيري" ضمن ظروف محكمة - دواي, فيصل; استنبولي, أحمد; عباس, خلود (Latakia University Journal -Biological Sciences Series, 2018)
The experiment was done to investigate the germination of seeds and embryos of Olea europaea “Alkhdery” in the Germination Laboratory- Faculty of Agriculture- Tishreen University during 2016-2017. The Study consisted of multiple experiments ,each of which consisted of many treatments . Every treatment had 3 replicates , where one had 10 seeds/embryos . The planting was performed on Agar medium 0.8%. The results showed that the ideal temperature for the germination of olive seeds was 13 c°. However , the rhythm of germination decreased when the temperature went beyond or below 13c° and stopped at 5c° and 25 c°. The ideal temperature for the germination of embryos was 13c° . However , many embryos germinate early at 20 or 25 c° with sharp decrease in the germination level . As for kernels the results showed that they couldn’t germinate at 13 c° due to their hard coats which stopped the entrance of water and oxygen. Also , the germination of seeds lagged behind that of the embryos due to the Endosperm coat which covered the embryos and stopped the passage of water and oxygen .In addition to that, it contained materials that crippled the germination process . أٌجريت الدراسة على انبات بذور وأجنة الزيتون "صنف الخضيري" في مخبر الانبات العائد لكلية الزراعة – جامعة تشرين خلال الأعوام 2016-2017 شملت الدراسة عدة تجارب ، وكل تجربة عدة معاملات في كل منها (3) مكررات ، ولكل مكرر(10) أفراد /جنين ،بذرة/ ، وتمت الزراعة على وسط آجار – آجار بتركيز 0.8%. أظهرت الدراسة أن الدرجة المثلى لانبات الزيتون صنف الخضيري هي 13 م° ، وكلما ابتعدت درجة الحرارة عن هذه الدرجة تنخفض وتيرة الانبات ، إلى أن تتوقف عند درجتي الحرارة 5 وَ 25 م° . كما تبين النتائج أن الدرجة المثلى لإنبات الجنين هي 13 م° ، أيضاً مع الإشارة إلى أنَّ جزء من الأجنة قد تمكن من الانبات بصورة مبكرة على حرارة 20- 25 م° مقارنة ً مع الانبات على حرارة 13 م°، لكن ترافق ذلك مع انخفاض واضح في نسبة الانبات. أظهرت النتائج أيضاً عند دراسة تأثير الأغلفة في الإنبات انعدام إنبات النوى على حرارة 13 م°؛ بسبب وجود أغلفة صلبة تعيق امتصاص الماء والأوكسجين ، وكذلك تأخر انبات البذور بالمقارنة مع الأجنة بسبب وجود غلاف الإندوسبرم الذي يحيط بالجنين والذي بدوره يؤخر دخول الماء والأوكسجين إضافةً لاحتوائه مواد مانعة للانبات.